Enhancing Learners Autonomy: Effects of an English Camp Program - Adara, Reza Anggriyashati; Victorynie, Irnie; Hamer, Welliam; Rohimajaya, Nur Azmi (Ta'dib, 2024)
Immersing learners in English can be a strategy to improve their autonomy in in English as a foreign language (EFL) learning. The objective of the present study is to analyze the improvement in factors related to learners’ autonomy after the English camp, one of types of language immersion programs. This study used a convenience sampling method. The participants consisted of thirty high school students. Therefore, the present study employed a quantitative research design by distributing a set of questionnaires before and after an-eight-day English camp program. The results suggest that the most salient factor that improves after the treatment is ‘important strategies’  (m=3.6 to m=3.75) while factors related ‘the learners’ sense of self-efficacy’ (m=3.75 to m=3.91) and ‘the role of teacher’ (m=3.47 to m=3.5) do not suggest a drastic increase. In contrast, the items related to ‘the role of the feedback’ (m=3.77 to m=3.58) show a decline. In this sense, the participants seem able to employ various important strategies to advance their language learning progress and improve their confidence while finding the roles of feedback they obtained during the program lessened. The results of this study imply the needs to provide comprehensible inputs to the students so that they can enhance their autonomy. The next study should involve the investigation of the effects of comprehensible inputs in an English camp toward learners’ autonomy.